Killer plants and fungi in horror cinema - Rasia, Luciano Luis (2022)
Animals have been the focus of horror films since the very beginning of the genre, with more than 400 films about killer animals to date. That is not the case for other two “Kingdoms” of life – Plantae and Fungi – despite many plants and fungi representing a danger to humans due to their poisonous nature. Nevertheless, some plants (e.g., carnivorous plants) and fungi (e.g., zombie-insect fungus) have inspired a handful of horror movies because of their bizarre manner to kill animals (although not humans). In this work I analyze horror films about killer plants and fungi, attempting a classification of them.